Embroidery from the Arabian Peninsula - Vogelsang-Eastwood, Gillian (Proceedings of the Seminar for Arabian Studies, 2017)
This article is a brief survey of the design forms of, and the social and economic contexts associated with, embroidery from the Arabian Peninsula in the twentieth century. It is intended to show how embroidery is a reflection of Arab life, as well as being an important part of the cultural heritage of this part of the world. The article also briefly looks at the main uses and types of embroidery to be found in the Peninsula, but with the emphasis that this is intended to be a summary of the main styles and does not include all the forms or details in depth. The information provided in this article is derived from an international project based at the Textile Research Centre, Leiden, into the history, range, and use of embroidery within the Arab cultural sphere. This project culminated in a book, edited by the present author (2016).